Identification of the factors that control synthesis and accumulation of a therapeutic protein, human immune‐regulatory interleukin‐10, in Arabidopsis thaliana. Issue 5 (10th January 2013) - Chen, Ling; Dempsey, Brian R.; Gyenis, Laszlo; Menassa, Rima; Brandle, Jim E.; Dhaubhadel, Sangeeta
Summary Plants are one of the most economical platforms for large‐scale production of recombinant proteins for biopharmaceutical and industrial uses. A large number of human recombinant proteins of therapeutic value have been successfully produced in plant systems. One of the main technical challenges of producing recombinant proteins in plants is to obtain sufficient level of protein. This research aims to identify the factors that control synthesis and accumulation of recombinant proteins in stable transgenic plants. A stepwise dissection of human immune‐regulatory interleukin‐10 (IL‐10) protein production was carried out using Arabidopsis thaliana as a model system. EMS‐mutagenized transgenic Arabidopsis IL‐10 lines, at2762 and at3262, produced significantly higher amount of IL‐10 protein than the non‐mutagenized IL‐10 line (WT‐IL‐10). The fates of trans‐gene in these sets of plants were compared in detail by measuring synthesis and accumulation of IL‐10 transcript, transcript stability, protein synthesis and IL‐10 protein accumulation. The IL‐10 transcripts were more stable in at2762 and at3262 lines than WT‐IL‐10, which may contribute to higher protein synthesis in these lines. To evaluate whether translational regulation of IL‐10 controls its synthesis in non‐mutagenized WT‐IL‐10 and higher IL‐10 accumulating mutant lines, we measured the efficiency of the translational machinery. Our results indicate that mutant lines with higher trans‐gene expression contain more robust and efficient translational machinery compared with the control line.